2013
DOI: 10.3390/molecules18088945
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Urokinase Type Plasminogen Activator and Cytostatic Activity from Crude Plants Extracts

Abstract: In view of the clear evidence that urokinase type plasminogen activator (uPA) plays an important role in the processes of tumor cell metastasis, aortic aneurysm, and multiple sclerosis, it has become a target of choice for pharmacological intervention. The goal of this study was thus to determine the presence of inhibitors of uPA in plants known traditionally for their anti-tumor properties. Crude methanol extracts were prepared from the leaves of plants (14) collected from the subtropical dry forest (Guanica,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…These findings suggest that these species can act as hemostatics by impeding the fibrinolysis process, and diverse potential uPA inhibitors may occur in these medicinal species. These outcomes are in agreement with a prior study on uPA inhibition activity of a Euphorbiaceae species, Croton lucidus , which showed a pronounced half‐maximal inhibitory effect against urokinase 33 . Furthermore, it was established that the oral administration of A. australis extracts regulates fibrinolysis and decreases platelet numbers, which account for the species' hemostatic effect 30 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These findings suggest that these species can act as hemostatics by impeding the fibrinolysis process, and diverse potential uPA inhibitors may occur in these medicinal species. These outcomes are in agreement with a prior study on uPA inhibition activity of a Euphorbiaceae species, Croton lucidus , which showed a pronounced half‐maximal inhibitory effect against urokinase 33 . Furthermore, it was established that the oral administration of A. australis extracts regulates fibrinolysis and decreases platelet numbers, which account for the species' hemostatic effect 30 .…”
Section: Resultssupporting
confidence: 90%
“…These outcomes are in agreement with a prior study on uPA inhibition activity of a Euphorbiaceae species, Croton lucidus, which showed a pronounced halfmaximal inhibitory effect against urokinase. 33 regulates fibrinolysis and decreases platelet numbers, which account for the species' hemostatic effect. 30 As a result, this work contributes to the expanding repository of knowledge about the three Euphorbiaceae species' hemostatic properties.…”
Section: Upa Activity Of the Three Euphorbiaceae Extractsmentioning
confidence: 99%
“…It is very specific genotype due to high production of alkaloids in poppy‐heads, however, less‐favoured for consumption due to lower sensory parameters of seeds than special food cultivars. The IA_UR has been detected in extracts from many tropical plants and temperate medicinal plants such as Acer platanoides and Rhus typhina . Some commonly grown crops were also studied and were found to be interesting from the point of view of the IA_UR.…”
Section: Resultsmentioning
confidence: 99%
“…Docetaxel was used as the drug of interest due to the possible correlation with uPA changes post drug administration. During this initial test, we found a clear correlation between 64 Cu-NOTA-ATN-291 F­(ab′) 2 tumor uptake and uPA level measured by western blot (Figure ), although the uPA changes were not considered as statistically significant. Recent studies have continuously revealed the important roles of the uPA during the anticancer drug treatment, for example, sorafenib, gemcitabine, and anticancer plant-derived chemicals, among many others. These results further confirmed that 64 Cu-NOTA-ATN-291-F­(ab′) 2 could delineate the uPA expression level after a treatment plan was set, and this can be extremely useful to evaluate especially treatments available specifically against the uPA or uPAR system, since it can give an objective uPA information before any morphological or size changes in tissues.…”
Section: Discussionmentioning
confidence: 99%